Malaria in Children - Prevention and Management - Dramowski, Angela; Frigati, Lisa; Rabie, Helena; Cotton, Mark (Infectious Disorders - Drug Targets, 2013)
Malaria causes a quarter of all childhood deaths in Sub-Saharan Africa. Considerable gains in global malaria control have been achieved in the last decade but coverage of effective interventions remains low in areas of greatest malaria burden. Some countries have achieved reduced malaria related mortality through application of recent advances in malaria prevention and treatment of children. Artemisinin combination therapies (particularly artesunate) are highly efficacious and well-tolerated in children, although several alternative treatments are available. However, the evolution of drug resistance (including emerging resistance to artemisinin derivatives) threatens the success of malaria treatment programmes. This special issue review is aimed at paediatric clinicians in resource-poor settings and provides a summary of recent data from paediatric trials of malaria treatment and prevention interventions.
Keywords: malaria